An Assessment of the 2015–2017 Drought in Windhoek - van Rensburg, Pierre; Tortajada, Cecilia (Frontiers in Climate, 2021)
Namibia is considered the most arid country in Sub-Sahara Africa. In Windhoek, the capital city, accelerated population growth and expanding economic activities coupled with highly variable rainfall and multiyear droughts, have put an enormous stress on socio-economic development of the city in terms of the security of water supply. This paper offers a review of the 2015-2017 drought, the policy and governance decisions that were implemented, as well as the engagement with the public, industries and public institutions to achieve water saving targets. In addition, the Windhoek Drought Response Plan as a management tool to face the then drought, setting the basis for a preparedness response for future droughts is considered. The assessment end with lessons learnt for all sectors; lessons that can hopefully pave the way for more effective responses in future similar occurrences.